Avoiding disc collisions and nonlinear vibration of unbalanced rotors by means of position control of the rotor journal mounted in magnetorheological hydrodynamic bearings. (May 2023) - Zapoměl, Jaroslav; Ferfecki, Petr; Kozánek, Jan
Abstract: Rotors of rotating machines are often supported by hydrodynamic bearings. Imbalance, ground vibration, assembling inaccuracies, and eccentric position of the shaft journal in the bearing hole may result in collisions between the rotors and their casings if the gap between the rotating and stationary parts is narrow. This can be avoided by controlling the position of the rotor journal in the bearing hole by changing stiffness of the oil film. This method of controlling parameters of the lubricating layer is offered by application of magnetically sensitive fluids. A new design of magnetically controllable hydrodynamic bearing was developed. The magnetic flux is generated by an electric coil. It passes through the bearing housing, and the layer of lubricant and goes back to the coil core. Magnetic induction in the bearing gap is calculated by application of the Kirchhoff and Hopkinson laws. The pressure distribution in the oil layer is obtained by solving the Reynolds equation adapted to lubricants exhibiting yielding shear stress, the magnitude of which depends on magnetic induction. Results of the computational simulations showed that application of a magnetic field acting on magnetorheological lubricant in the bearing gap makes it possible to prevent impacts between the rotor and its casing in a certain velocity interval, or at least to reduce magnitude of the impact forces if collisions occur. The principal contribution of the conducted research is the proposal of a new approach based on semiactive principle to controlling position of rotors working in limited space and obtaining more information on interaction between the rotors and magnetically controllable hydrodynamic bearings during the operating conditions when collisions between the rotor and its stationary part take place. Highlights: Proposal of a new method for controlling position of a rotor operating in space with narrow gaps — original. Utilization of the change of the magnetorheological lubricant apparent viscosity by action of a magnetic field to control the rotor position, — original. Application of the original modification of the Reynolds equation adapted for liquids with yielding shear stress. Development of a mathematical model of a magnetically controllable rotor–bearing system, original. Obtaining deeper knowledge on mutual interaction between activated/deactivated magnetorheological bearings and rotors performing disc-casing impacts. Confirmation of applicability of the proposed new and original control method by means of computational simulations supported by experimental research.